Spontaneous Pneumothorax after Physical Exertion on Adolescets with Vaping History in Diponegoro National Hospital Semarang: A Case Report - Qonita Nur Qolby; Muzaki Wilastono; Hanifa Amalia Balqis; Hadi Hadi; Luqman Alwi (Diponegoro International Medical Journal, 2025)
Background: Vaping is now a trend for a tobacco-smoking alternative. However, studies and regulations regarding the side effects of vaping are limited. Recently, vaping-associated spontaneous pneumothorax cases were reported. Pneumothorax, when air accumulates in the pleural cavity, could progress to an emergency case. It is rarely related to physical exercise.Case Presentation: We found two spontaneous pneumothorax cases in Diponegoro National Hospital that presented with chest pain and cough post-exercise in vaping adolescents. The diagnosis was established based on medical history, physical examination, and chest X-ray. Both patients were treated with water-sealed drainage (WSD) and intensive care.Conclusion: Pneumothorax is an important diagnosis to consider in vaping patients, resulting in long stay and high-cost hospitalization. Vaping-associated spontaneous pneumothorax cases in active adolescents should receive special attention for conducting electronic cigarette studies and regulations in Indonesia.